CEBPB regulates the migration, invasion and EMT of breast cancer cells by inhibiting THBS2 expression and O-fucosylation - Qi, Liqiang; Sun, Bo; Yang, Beibei; Lu, Su (Human Molecular Genetics, 2023)
Abstract Breast cancer (bc) is the second most common type of human malignancies with highest morbidity and mortality in the female population. Therefore, it is essential to develop novel and effective therapies for bc treatment. The main aim of the current study is to investigate the functions of CEBPB and THBS2 in bc and the underlying mechanism. Reverse transcription–quantitative real-time polymerase chain reaction and western blot were performed for the measurement of ribonucleic acids and proteins. Function and mechanism assays were, respectively, conducted for the evaluation of bc biological behaviors and exploration of the potential correlation of genes. According to bioinformatics analyses and experimental results, THBS2, up-regulated in bc tissues and cell lines, could facilitate cell migration, invasion and EMT in bc. CEBPB was validated to facilitate miR-29a-3p transcription, thus negatively modulating THBS2 expression. The results of rescue experiments reflected that CEBPB could regulate the malignant behaviors of bc cells via THBS2. Furthermore, CEBPB was ascertained to inhibit the transcription of B3GALTL to affect THBS2 protein O-fucosylation and secretion. The interaction between THBS2 and ITGB1 was confirmed, and THBS2 was found to activate the PI3K/AKT signaling pathway. To conclude, CEBPB could restrain bc cell migration, invasion and EMT via inhibition on THBS2 expression and O-fucosylation. Graphical Abstract Graphical Abstract